2019
DOI: 10.1021/jacs.9b09127
|View full text |Cite
|
Sign up to set email alerts
|

Histidine-Specific Peptide Modification via Visible-Light-Promoted C–H Alkylation

Abstract: Histidine (His) carries a unique heteroaromatic imidazole side chain and plays irreplaceable functional roles in peptides and proteins. Existing strategies for site-selective histidine modification predominantly rely on the N-substitution reactions of the moderately nucleophilic imidazole group, which inherently suffers from the interferences from lysine and cysteine residues. Chemoselective modification of histidine remains one of the most difficult challenges in peptide chemistry. Herein, we report peptide m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(98 citation statements)
references
References 55 publications
1
97
0
Order By: Relevance
“…These efforts have been extensively reviewed [1–5] . More recently, several more of these methods have been reported that utilize novel functional groups to demonstrate impressive chemoselectivity to Cys, [6–9] Lys, [10–13] His, [14–16] Met, [17–19] Trp, [20] and Tyr [21] …”
Section: Overview Of Protein Modification Methodsmentioning
confidence: 99%
“…These efforts have been extensively reviewed [1–5] . More recently, several more of these methods have been reported that utilize novel functional groups to demonstrate impressive chemoselectivity to Cys, [6–9] Lys, [10–13] His, [14–16] Met, [17–19] Trp, [20] and Tyr [21] …”
Section: Overview Of Protein Modification Methodsmentioning
confidence: 99%
“…Conversely, by switching to MeCF 2 SO 2 Na, the corresponding difluoroethylation took place selectively at the His unit. Likewise, the reactivity pattern wherein aromatic His residue was selectively modified in the presence of Trp and Tyr residues was also observed when utilizing non‐fluorinated alkyl radical precursors . Although the mechanism of these trifluoromethylation reactions are not commented in the original publications, a plausible scenario would likely entail a Minisci‐type C−H functionalization step of the imidazole core with the ensuing electrophilic radical species …”
Section: Trifluoromethylation Of Peptidesmentioning
confidence: 97%
“…20). 37 It is believed that homolytic cleavage of the C-C bond in a Hantzsch ester, dihydropyridine (DHP) alkylating reagent occurs under visible light irradiation. The alkyl radical formed can then attack a protonated histidine imidazole ring.…”
Section: Aromatic Amino Acid Side Chainsmentioning
confidence: 99%